2014
DOI: 10.1136/bjophthalmol-2013-304636
|View full text |Cite
|
Sign up to set email alerts
|

Cambridgeshire cataract shared care model: community optometrist-delivered postoperative discharge scheme

Abstract: Postcataract surgery follow-up by community optometrists provides the advantages of care closer to home and avoids unnecessary hospital visits for patients undergoing uncomplicated cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…Feedback is essential to the compulsory audit of outcomes following NHS cataract surgery and should form an integral part of the service‐level agreement. Feedback return rates have not been routinely reported in the literature . Our scheme, however, illustrates that high rates can be achieved.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Feedback is essential to the compulsory audit of outcomes following NHS cataract surgery and should form an integral part of the service‐level agreement. Feedback return rates have not been routinely reported in the literature . Our scheme, however, illustrates that high rates can be achieved.…”
Section: Discussionmentioning
confidence: 75%
“…The value of 85% of patients listed was derived as an achievable target from previously reported studies . Postoperative feedback of 90% was derived from the audit standard used in our review of the optometrist‐delivered postoperative discharge scheme previously reported in literature …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations